Single-nucleus transcriptomics reveal the cytological mechanism of conjugated linoleic acids in regulating intramuscular fat deposition - Liyi Wang; Shiqi Liu; Shu Zhang; Yizhen Wang; Yanbing Zhou; Tizhong Shan (eLife)
Conjugated linoleic acids (CLAs) can serve as a nutritional intervention to regulate quality, function, and fat infiltration in skeletal muscles, but the specific cytological mechanisms remain unknown. Here, we applied single-nucleus RNA-sequencing (snRNA-seq) to characterize the cytological mechanism of CLAs regulates fat infiltration in skeletal muscles based on pig models. We investigated the regulatory effects of CLAs on cell populations and molecular characteristics in pig muscles and found CLAs could promote the transformation of fast glycolytic myofibers into slow oxidative myofibers. We also observed three subpopulations including SCD+/DGAT2+, FABP5+/SIAH1+, and PDE4D+/PDE7B+ subclusters in adipocytes and CLAs could increase the percentage of SCD+/DGAT2+ adipocytes. RNA velocity analysis showed FABP5+/SIAH1+ and PDE4D+/PDE7B+ adipocytes could differentiate into SCD+/DGAT2+ adipocytes. We further verified the differentiated trajectory of mature adipocytes and identified PDE4D+/PDE7B+ adipocytes could differentiate into SCD+/DGAT2+ and FABP5+/SIAH1+ adipocytes by using high intramuscular fat (IMF) content Laiwu pig models. The cell-cell communication analysis identified the interaction network between adipocytes and other subclusters such as fibro/adipogenic progenitors (FAPs). Pseudotemporal trajectory analysis and RNA velocity analysis also showed FAPs could differentiate into PDE4D+/PDE7B+ preadipocytes and we discovered the differentiated trajectory of preadipocytes into mature adipocytes. Besides, we found CLAs could promote FAPs differentiate into SCD+/DGAT2+ adipocytes via inhibiting c-Jun N-terminal kinase (JNK) signaling pathway in vitro. This study provides a foundation for regulating fat infiltration in skeletal muscles by using nutritional strategies and provides potential opportunities to serve pig as an animal model to study human fat infiltrated diseases.